The Impact of FinTech Partnerships on Banking Digitalization and Post-Crisis Economic Resilience - Hun, Yan; Bashir, Abdul; Raza, Muhammad (Journal of Business and Economic Options, 2024)
The primary objective of this research is to examine the role of banking digitalization in driving economic recovery, with a specific focus on how collaboration with the FinTech industry can enhance this process. Additionally, this research will analyze the challenges and opportunities posed by such collaborations, considering regulatory frameworks, technological advancements, and consumer adoption patterns to provide a comprehensive understanding of the potential impact of banking digitalization on post-crisis economic resilience. The core result of this empirical study demonstrates that the FinTech industry exerts a significant influence in both mediating and moderating the relationship between banking digitalization and national economic recovery. The findings reveal that the FinTech industry acts as a crucial intermediary that enhances the impact of digitalization efforts within the banking sector, amplifying their contribution to economic recovery. Additionally, the study shows that FinTech has the potential to strengthen the effectiveness of digital banking initiatives by providing innovative solutions, improving customer access to financial services, and increasing the overall efficiency of banking operations. Collaboration between traditional banks and FinTech companies has emerged as a key factor in accelerating digital transformation, which is essential for fostering economic resilience and recovery. By embracing FinTech innovations, banks can expand their digital offerings, improve the customer experience, streamline transactions, and reduce operational costs. This partnership approach not only boosts the competitiveness of individual financial institutions but also contributes to broader national economic recovery efforts by promoting financial inclusion, expanding access to credit, and driving sustainable growth. Furthermore, the research provides valuable insights into how banks can leverage FinTech solutions to overcome the challenges posed by rapidly changing market conditions, technological advancements, and evolving customer expectations. It highlights the importance of creating a supportive regulatory environment and developing innovative collaboration models that enable both traditional financial institutions and FinTech firms to thrive. This study makes a substantial contribution to the banking sector by offering a roadmap for accelerating digital transformation through strategic partnerships with FinTech companies, thereby positioning the industry as a key player in driving national economic recovery. Ultimately, the research underscores the importance of integrating FinTech into the banking ecosystem, showing that such collaboration is not only beneficial but necessary for future growth. By fostering a seamless blend of traditional banking expertise and FinTech innovation, the industry can create more resilient, flexible, and customer-centric financial services that are capable of responding to both current and future economic challenges. The findings of this study thus provide a clear pathway for banks looking to accelerate their digital transformation and actively participate in the nation's economic recovery efforts.